2016
DOI: 10.1172/jci.insight.88198
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural alterations of sputum in cystic fibrosis lung disease

Abstract: The stasis of mucus secretions in the lungs of cystic fibrosis (CF) patients leads to recurrent infections and pulmonary exacerbations, resulting in decreased survival. Prior studies have assessed the biochemical and biophysical features of airway mucus in individuals with CF. However, these measurements are unable to probe mucus structure on microscopic length scales relevant to key players in the progression of CF-related lung disease, namely, viruses, bacteria, and neutrophils. In this study, we quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(135 citation statements)
references
References 53 publications
5
130
0
Order By: Relevance
“…Second, if the NP used were muco-inert, the magnetic force may have caused the NP to run into mucus bundles, causing them to potentially deform around and trap the particles or to enter mucus pores smaller than the particle diameter and rendered them sterically trapped. We have previously shown that various mucus samples exhibit highly heterogeneous pore size distributions, with significant percentages of pores smaller than the size of conventional NP ( 25 , 26 , 53 56 ). In addition, NP were under a constant unidirectional magnetic force, such that NP that entered into small mucus pockets would be unlikely to escape.…”
Section: Discussionmentioning
confidence: 99%
“…Second, if the NP used were muco-inert, the magnetic force may have caused the NP to run into mucus bundles, causing them to potentially deform around and trap the particles or to enter mucus pores smaller than the particle diameter and rendered them sterically trapped. We have previously shown that various mucus samples exhibit highly heterogeneous pore size distributions, with significant percentages of pores smaller than the size of conventional NP ( 25 , 26 , 53 56 ). In addition, NP were under a constant unidirectional magnetic force, such that NP that entered into small mucus pockets would be unlikely to escape.…”
Section: Discussionmentioning
confidence: 99%
“…64 Recently, we have confirmed that increased DNA levels in CF mucus correlates with reduced mucus mesh size. 71 Recombinant human DNase (Pulmozyme) is a commonly used mucolytic compound that reduces CF mucus viscoelasticity upon inhalation by cleaving DNA oligomer chains. 70 Increased levels of actin may also enhance mucus barrier properties, as gelsolin treatment, which depolymerizes actin, greatly reduces the viscoelastic properties of CF airway secretions.…”
Section: Mucus In Individuals With Lung Diseasementioning
confidence: 99%
“…71,74,75 The diffusion of polystyrene (PS) nanoparticles (NP) and antibioticloaded liposomes is greatly hindered within the extracellular matrix of biofilms produced by bacteria commonly found in the lungs of CF patients, including Pseudomonas aeruginosa and Burkhedia cepacia complex. [76][77][78] As such, bacterial biofilms may represent an additional extracellular barrier component unique to CF airway mucus that must be overcome by inhaled gene vectors.…”
Section: Mucus In Individuals With Lung Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate mucus directly on mouse airway surfaces, we employed MPT to quantify MSD of muco-inert nano-particles (MIPs) aerosolized onto mouse tracheas ex vivo [24][25][26] . Tracheas were removed from saline or AOE challenged mice, opened, placed on glass coverslips, and treated with nebulized 100 nm diameter MIPs suspended in saline vehicle or TCEP (Fig 2a).…”
mentioning
confidence: 99%